Gratifikasi Oleh Perusahaan Farmasi Terhadap Dokter Dalam Pelayanan Medis Di Rumah Sakit - Roni Pardamean Gultom; Alvi Syahrin; Madiasa Ablisar; Mahmud Mulyadi (Iuris Studia: Jurnal Kajian Hukum, 2022)
The occurrence of gratification in this day and age has entered all sectors without exception in the health sector, namely in the field of medicine. The existence of gratification carried out by pharmaceutical companies against doctors, namely where the pharmaceutical company in promoting drugs uses collusion in the form of cooperation with doctors by providing commissions or incentives to doctors for every drug prescription writing to patients where this is an agreement made between pharmaceutical companies with the doctor. There is an effect of giving something to a civil servant doctor by a pharmaceutical company so that the doctor's freedom and independence in writing prescriptions for patients is lost. Doctors tend to prescribe drugs made by pharmaceutical companies, which are something that is delicious to doctors, so that the drug is expensive and results in a monopoly and the need for consumer protection. The doctor can be qualified as a Gratification Crime as regulated in Article 12B